A Case with Tumor, Tuberculosis and Chylothorax - Cansiz, Kubra Asik; Tug, Tuncer; Konuk, Suat; Kilicgun, Haci Ali; Aydin, Suphi (Archives of Clinical and Medical Case Reports, 2018)
Chylothorax is a rare clinical condition caused by the accumulation of lymphatic fluid in the pleural space. Chylothorax often results in thoracic trauma and malignant obstruction. More rare causes are tuberculosis, infanjiomiyomatosis, venous thrombosis, congenital lymphatic malformation, nephrotic syndrome, hypothyroidism, cirrhosis, chemotherapeutic drugs, sarcoidosis and idiopathic chylothorax. A 77-year-old female patient with a one year history of colon cancer and post-op chemotherapy was referred to us with the suspicion of metastasis upon detection of lymphadenomas and pleural effusion during a thoracic CT in follow-up. Thoracentesis was performed for the pleural effusion of the patient and chylous fluid was aspirated. The diagnosis of chylothorax was confirmed by pleural fluid biochemical analysis. Results were consistent with tuberculosis from the biopsy performed on synchronous lymph nodes. Due to multiple causes in the etiology of chylothorax, we presented our case.